1986
DOI: 10.1111/j.1469-8749.1986.tb03879.x
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Muscle Training in Duchenne Muscular Dystrophy

Abstract: SUMMARY Eighteen boys with Duchenne muscular dystrophy were entered into trials to assess the effects of specific ventilatory strength and endurance training programmes. The findings showed an improvement in ventilatory muscle endurance but not in strength as a result of specific respiratory muscle training. The clinical significance of these findings is uncertain, however, and needs further evaluation. RÉSUMÉ Entrainement des muscles respiratoires dans la myopathie de Duchenne Des examens ont été effectúes po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

1988
1988
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 11 publications
0
21
0
1
Order By: Relevance
“…A common issue with both IOPD and LOPD is progressive restrictive ventilatory failure (1,26). Several forms of respiratory muscle exercise training have been successfully described in MD (27)(28)(29). More recently, several studies have shown that respiratory exercise training is helpful in PD (30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…A common issue with both IOPD and LOPD is progressive restrictive ventilatory failure (1,26). Several forms of respiratory muscle exercise training have been successfully described in MD (27)(28)(29). More recently, several studies have shown that respiratory exercise training is helpful in PD (30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…Previous ments in both strength and endurance were possible. Our own pilot study (Martin et al 1986) suggested that respiratory muscle training could improve endurance, but not strength or vital capacity. In that study improved endurance was based on the time that resistance to airflow could be tolerated, whereas in the present trial the Nickerson valve provided a more objective means of measuring endurance.…”
Section: Discussionmentioning
confidence: 93%
“…The physiotherapeutic management of these respiratory problems have included breathing exercises and 'blowing' games (Houser andJohnson 1971, Siege1 1975)' but there was little objective evidence that these measures had a significant effect on respiratory function or on eventual outcome. In order to assess whether it was possible to increase respiratory muscle strength and endurance by respiratory muscle training, we carried out a pilot project involving 18 boys with Duchenne dystrophy (Martin et al 1986). It showed that there was significant improvement in ventilatory muscle endurance, but not in strength.…”
mentioning
confidence: 99%
“…164 Several other authors also failed to induce gains of lung volumes in response to such training. [165][166][167][168] Possibly, the training period was too short. Winkler and associates 32 had 16 patients with neuromuscular dystrophy (13 with Duchenne dystrophy) undertake 9 months of home training, using a variable inspiratory resistance.…”
Section: Duchenne Muscular Dystrophymentioning
confidence: 99%